PERLINDUNGAN HAK ASASI MANUSIA DI INDONESIA DALAM DINAMIKA GLOBAL - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
Human rights have been often interpreted as a universal value by the developed countries. However. on he other side. there are common acceptance that every nations has their own human rights value with have particularistic character. I process of globalization. the dilemma between universal and particularistic value of human rights often manipulate by interest groups as political commodity/ bargain power to reach their own goals. This article tries to explain that theprocess of globalization with related to theprotection of human rights did not have monolithic. homogeneous. or uniform characters otherwise it wasfull of political. economical. and social dynamics interest.